Pendekatan Business Model Canvas (BMC) untuk Strategi Pengembangan UMKM Jajanan Tradisional Kota Padang - Triha, Hadigufri; Putri, Ranti Mustika (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to formulate a development strategy for traditional snack Micro, Small, and Medium Enterprises (MSMEs) in Padang City using the Business Model Canvas (BMC) approach. The unique challenges faced by traditional culinary businesses, such as competition from modern snacks and gaps in digitalization, necessitate a structured business model innovation. This research employed a qualitative descriptive method, involving in-depth interviews and observations with five traditional snack MSME owners in Padang. Data were analyzed by mapping the existing (as-is) BMC and conducting a SWOT analysis to identify internal and external factors. The results indicate that most MSMEs still operate conventionally, with weaknesses in the 'Channels' and 'Customer Relationships' elements. This study proposes a 'to-be' BMC, emphasizing the integration of digital channels (social media, e-commerce), strengthening 'Value Propositions' through authentic branding and modern packaging, and establishing 'Key Partnerships' with local suppliers and delivery services. The implication is a practical strategic framework for MSMEs to enhance competitiveness and sustainability.